(untitled) (Revista Electrónica REDINE, 2018)
The following educational experience is based on the development and subsequent implementation of the community project held in the community located at the center of Cabudare, in the Municipality of Palavecino, with the purpose that the Higher Education students put into practice their learning and teaching experience from their professional and human dimensions, to raise public awareness to visualize the importance of prevention in drug use and the spreading of AIDS to be healthy. This began with a participatory diagnosis, follwed by a design of an action plan with strategies and activities undertaken by all involved. It was based on a participatory action research methodology, taking into account origins, fundamentals, objectives with precise solutions to understand the reality of the environment. This implies that an adequate college preparation will expedite the best performance of students in community projects, providing effective solutions to the issues proposed for conscious prevention.